2010
DOI: 10.1007/s11270-009-0310-7
|View full text |Cite
|
Sign up to set email alerts
|

The Development of SPE Procedures and an UHPLC Method for the Simultaneous Determination of Ten Drugs in Water Samples

Abstract: Analytical procedures for the determination of pharmaceuticals from different therapeutic groups were proposed. These groups included the corticosteroids prednisolone and dexamethasone; the β-blockers sotalol, metoprolol, propranolol, and carvedilol; and the analgesic nonsteroidal antiinflammatory drugs paracetamol, aspirin, metamizole, and ketoprofen. Reversed-phase ultrahigh performance liquid chromatography with an ultraviolet detector, different columns, different mobile phases, and gradient elution progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The results showed that the HLB column packing polymer had a good effect on purification, followed by operational simplicity and better reproducibility, and some published reports (Kamoda et al . ; Baranowska and Kowalski ) also confirm this result. Four millilitres of leachate (ultrapure water) and 3 mL of eluent (ammonia: methanol, 25:75, v/v) could improve the purification effect when the sample solution was added to the Oasis HLB column.…”
Section: Resultssupporting
confidence: 55%
“…The results showed that the HLB column packing polymer had a good effect on purification, followed by operational simplicity and better reproducibility, and some published reports (Kamoda et al . ; Baranowska and Kowalski ) also confirm this result. Four millilitres of leachate (ultrapure water) and 3 mL of eluent (ammonia: methanol, 25:75, v/v) could improve the purification effect when the sample solution was added to the Oasis HLB column.…”
Section: Resultssupporting
confidence: 55%
“…The literature surveys revealed a number of already developed techniques for determining PC in different samples [15]. These techniques include titrimetric determination [16][17][18], liquid chromatography-mass spectroscopy [19][20], high performance-liquid chromatography [21][22], liquid chromatography [23], capillary electrophoresis [24], chemiluminescence [25], UV-Vis spectrometry [26][27], infrared spectroscopy [28], and flow [29][30] and batch [31] injection analyses. These methods offer high sensitivity, selectivity and accuracy, but difficulties of their use such as time-consuming measurement process, highly expert technicians required for the operation, and high cost instruments, limit their extensive applications.…”
Section: Introductionmentioning
confidence: 99%
“…Polar, non-volatile or thermally degradable compounds and their derivatives cannot be analysed by GC, and LC is an essential tool for the analysis of these types of compounds (Chen et al 2008;Castiglioni et al 2005). Liquid chromatography with tandem-mass spectrometry (LC-MS/MS) is the most commonly used technique (Wu et al 2008;Baranowska and Kowalski 2010;Gros et al 2012).…”
Section: Introductionmentioning
confidence: 99%